Dampak Dispersion Of Ownership, Financial Distress, Dewan Pengawas, Umur Listing terhadap Pengungkapan Sukarela Bank Syariah - Alfian, Barry; Handajani, Lilik; Nugraha Ardana Putra, I Nyoman (E-Jurnal Akuntansi, 2020)
This study aims to look at the effect of ownership dispersion, financial distress, sharia supervisory board and age of listings on the extent of voluntary disclosure in Islamic banks registered with OJK in the 2015-2018 period. The population of the study was 14 companies of Islamic Commercial Banks and the number of samples obtained were 13 companies with an observation period of 4 years. Data analysis techniques using multiple linear regression. Statistical results show that Simultaneous that dispersion of ownership, financial distress, sharia supervisory board and age of listings have a positive and significant effect on voluntary disclosure of Islamic Commercial Banks. While partially dispersion of ownership and sharia supervisory board negative significant influence on voluntary disclosure of Islamic Commercial Banks. Keywords: Voluntary Disclosure; Ownership Dispersion; Financial Distress; Supervisory Board; Age Of Listing.